T null and M null genotypes of the glutathione S-transferase gene are risk factor for CAD independent of smoking - Mohamed Gamal H; Al-Boudari Olayan M; Abu-Amero Khaled K; Dzimiri Nduna (BMC Medical Genetics, 2006)
Abstract Background The association of the deletion in GSTT1 and GSTM1 genes with coronary artery disease (CAD) among smokers is controversial. In addition, no such investigation has previously been conducted among Arabs. Methods We genotyped 1054 CAD patients and 762 controls for GSTT1 and GSTM1 deletion by multiplex polymerase chain reaction. Both CAD and controls were Saudi Arabs. Results In the control group (n = 762), 82.3% had the T wild M wildgenotype, 9% had the Twild M null, 2.4% had the Tnull M wild and 6.3% had the Tnull M null genotype. Among the CAD group (n = 1054), 29.5% had the Twild M wild genotype, 26.6% (p < .001) had the Twild M null, 8.3% (p < .001) had the Tnull M wild and 35.6% (p < .001) had the Tnull M null genotype, indicating a significant association of the Twild M null, Tnull M wild and Tnull M null genotypes with CAD. Univariate analysis also showed that smoking, age, hypercholesterolemia and hypertriglyceridemia, diabetes mellitus, family history of CAD, hypertension and obesity are all associated with CAD, whereas gender and myocardial infarction are not. Binary logistic regression for smoking and genotypes indicated that only M null and Tnullare interacting with smoking. However, further subgroup analysis stratifying the data by smoking status suggested that genotype-smoking interactions have no effect on the development of CAD. Conclusion GSTT1 and GSTM1 null-genotypes are risk factor for CAD independent of genotype-smoking interaction.